History of the Singapore Police Force : community policing in high-rise Singapore - Woon, Javier Wei Quan (Nanyang Technological University, 2020)
This paper intends to study why community policing was implemented in high-rise Singapore. As such, this paper seeks to examine the historical relationship between Singapore’s transition from low-rise to high-rise living and the adoption of community policing in Singapore. In particular, this paper contends that there were three facets of change – spatial, social and political – during Singapore’s transition from low-rise to high-rise living. Cumulatively, these changes necessitated a rethink of policing strategies and ushered in the era of community policing in high-rise Singapore. As such, this paper argues that community policing was implemented to address spatial, social and political changes that occurred during Singapore’s transition from low-rise to high-rise housing. Spatially, community policing made it physically possible for SPF to provide ubiquitous police coverage across the growing numbers of high-rise HDB estates scattered throughout the island. Socially, community policing mended broken down inter- and intra-family social dynamics through crime prevention initiatives built on improved police-public relationship. Politically, community policing can be understood as a subset of the broader government objective of nation-building through HDB public housing flats; community policing helped ensured long-term stability through political legitimisation, surveillance and citizenry identity-building.